Morphology of Femur, Tibiotarsus and Fibula of Local Hill Fowl of Uttarakhand - Tamilselvan, S.; Jaiswal, Pallavi; Mrigesh, Meena; Singh, Balwinder; Mahanta, Dwipjyoti (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
This study was conducted on femur, tibiotarsus and fibula from six adult local hill fowl of Uttarakhand. The femur of the local hill fowl was a long cylindrical bone consisted of a shaft and two extremities. The shaft was curved and twisted in appearance. The proximal extremity had spherical head separated from shaft by neck. The trochanter minor was indistinct. The distal extremity had posteriorly medial and lateral condyles and anteriorly trochlea. The tibiotarsus was the longest bone among the leg bones. The shaft was anteriorly curved in its proximal half and posteriorly curved in its distal half. The fibular crest was well developed and on posterior-lateral aspect of it’s mid shaft very small nutrient foramen was observed. The cnemial crest was originates from cranial border of transverse ridge and extended ventro-medially. The distal extremity showed large medial and small lateral condyles separated by the deep intercondyler fossa. The fibula was a reduced long bone with distinct head and rudimentary shaft. The shaft of fibula extended up to the distal one third of the shaft of tibiotarsus.